New sulfonate Gemini surfactants: synthesis and evaluation for enhanced oil recovery applications. Issue 14 (1st December 2020) - Mpelwa, Musa; Tang, Shanfa; Jin, Lijun; Hu, Ruizhi
Abstract: In this work, a series of new sulfonate Gemini surfactants (abbreviated as m-3-m) were studied as an attempt to develop a single surfactant that can effectively reduce the oil-water interfacial tension to ultralow values. The novel surfactants were synthesized and characterized by 1 HNMR and 13 CNMR spectroscopies. The surface activeness of those surfactants at the air-water interface and thermodynamic properties in the bulk aqueous phase were investigated. The oil-water interfacial tension, viscous and viscoelastic properties of solutions were studied. The results showed that the novel surfactants exhibit fascinating surface activeness and low values of CMC; spontaneously formed micelles and adsorbed at the air-water interface. They can substantially reduce the oil-water interfacial tension to ultralow values ( 10 − 3   mN / m ) when the surfactant concentration is less than 0.5 wt%. The surfactants possess attractive viscous and viscoelastic properties towards EOR applications through flooding methods. In accordance with the experimental studies, the surfactants are promising in formulating fluid systems with ultralow interfacial tension. Graphical Abstract: uf0001